Rethinking ADHD as a neurointestinal syndrome: a gut–brain–parasite hypothesis - Demas, Alexis (Frontiers in Neuroscience, 2026)
Neurodevelopmental conditions such as Attention-Deficit/Hyperactivity Disorder (ADHD) are usually framed as brain-based disorders driven by genetics and neurotransmitter imbalance. At the same time, converging evidence implicates the gut–brain axis and intestinal immunity in shaping cognition and behavior. In this Hypothesis and Theory article, I propose that a subset of ADHD and related neurodivergent profiles can be usefully conceptualized as neurointestinal syndromes, emerging from co-evolutionary interactions between the gut microbiota, intestinal parasites, and host immunity. Drawing on data from ADHD, autism spectrum conditions, and migraine, I synthesize evidence for altered microbiota, increased intestinal permeability, and low-grade inflammation in neurodivergent individuals, and discuss how these changes may bias tryptophan metabolism, vagal signaling, and large-scale brain networks. I then explore a speculative evolutionary scenario in which recurrent helminth exposure, historically ubiquitous, acted as a long-term ecological force shaping gut architecture, immunoregulation, and stress responsivity. Chronic parasitic pressure, combined with microbial metabolites and epigenetic imprinting, may have contributed to the emergence of attentional profiles characterized by hypervigilance, novelty seeking, and rapid switching—traits that could have been advantageous in ancestral, pathogen-rich environments but are often maladaptive in modern settings. This framework does not romanticize ADHD nor deny its frequent clinical burden. Rather, it reframes some ADHD phenotypes as possible mismatch syndromes involving the gut–brain axis, generated when an evolutionarily tuned intestinal and immune architecture is placed in sanitized, post-industrial ecologies. Clinically, this perspective supports continued use of established CNS-targeted treatments while motivating complementary research into microbial, barrier, and vagal interventions as potential adjuncts for carefully defined ADHD subgroups.